Asymmetric cointegration between exchange rate and trade balance in Nigeria - Alhaji Jibrilla Aliyu; Shehu Mohammed Tijjani (Cogent Economics & Finance, 2015)
This paper empirically examines the long-run pass through of the official exchange rates into trade balance in Nigeria by means of threshold cointegration and asymmetric error correction modeling. The study provides evidence for non-linear cointegration between our variables of interest. The estimated asymmetric error correction models provide new evidence for slower transmission of exchange rate depreciations into the country's trade balance, which in turn appears to offer partial support for the Dutch disease hypothesis. This finding suggests that policy-makers cannot hope to use currency devaluation to improve the trade balance. It is recommended that policy-makers focus attention on diversification of the economy away from dependence on crude oil exports into productive manufacturing and non-oil exports, which will be vital in making the economy more competitive.
Keywords: F4; F41; C22; 330; exchange rate; trade balance; Dutch disease hypothesis; threshold autoregression; asymmetric adjustment; causality autoregressive; causality